Analisis Molekuler dan Morfologi P. amabilis Transgenik dengan Gen Pembungaan PaFT - Ida Ayu Purnama Bestari (Jurnal Pendidikan Biologi Undiksha, 2022)
Phalaenopsis amabilis (L.) Blume or moon orchid is a type of orchid that has high economic and aesthetic value, but the flowering time is relatively long. Induction of flowering was carried out by inserting the PaFT gene with the ubiquitin promoter in the plant to obtain transgenic candidate plants (transformants). Transformant plants were grown in New Phalaenopsis (NP) medium for 40 weeks. Molecular analysis on transformant plants obtained P. amabilis transgenic. Amplification with ubiquitin (forward) and T-Nos (reverse) and deg PaFT primers in transgenic plants obtained DNA sequences of 1137 bp and 533 bp, while for non-transformant plants with deg PaFT primers, DNA bands of 1500 bp were obtained. The development of transgenic and non-transformant plants were then compared at 10, 20, 30, and 40 weeks of age. The results showed that transgenic plants produced multiple shoots/multishoots and longer roots compared to the roots of non-transformant plants. According to the literature study, there are morphological differences in some plants that carry the flowering locus T gene compared to nontransforman/wildtype plants.